Reconstruction of Village Head Election Dispute Settlement - Wijayanti, Septi Nur; Prasetyoningsih, Nanik; Lailam, Tanto; Iswandi, Kelik (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 1 (2024)DO - 10.24843/JMHU.2024.v13.i01.p01, 2024)
The resolution of disagreements regarding the outcomes of the village head election is still a topic of debate at this time. The resolution of complaints over the outcomes of the village head election must comply with Law Number 6 of 2014 Concerning Villages, however, the regent holds a political office and is therefore particularly susceptible to the independence of conflict resolution. In this study, the regent's handling of village head election issues was examined using the principle of the separation of powers. This normative legal research looked at elementary, secondary, and tertiary legal materials to address these issues. The results of this study indicated that the position of the regent is part of the executive branch of power, so it does not have the authority to judge. Therefore, the regent must form a dispute resolution team consisting of community leaders who have the capability to resolve disputes. The decision from the team is binding, and if there is still a candidate for village head who does not accept it, they can submit a legal process to the State Administrative Court.